KINERJA KEUANGAN, RISIKO, DAN RETURN SAHAM PADA PERBANKAN DI INDONESIA - Ridhasyah, Rizki; Kareem, Yunesta Anugiatama; Andanawarih, Parasdya Pandhu (Universitas YPPI Rembang, 2023)
This research contributes to examine the effect of Financial Performance and Risk on Stock Returns in banking companies in Indonesia. This study attempts to incorporate elements of financial performance and risk as they are closely related to the fluctuations of stock prices through the financial contributions of banks and the challenges they face. A sample of 39 banking companies listed on the Indonesia Stock Exchange was selected for the observation period of 2018-2021, resulting in 156 observation data. Financial Performance was proxied using Return on Assets (ROA), Debt to Equity Ratio (DER), Cash Ratio (CR), and Total Assets Turnover (TATO). Risk was measured using Non-Performing Loan (NPL), Net Interest Margin (NIM), Capital Adequacy Ratio (CAR), and Loan to Deposit Ratio (LDR). The results of this study indicate that financial performance, proxied by ROA and CR, has a negative effect on stock returns. In contrast, DER and TATO do not have a significant impact and have a positive effect on stock returns, respectively. The research also provides information that risk, measured by NPL, NIM, and LDR, does not have a partial influence on stock returns, whereas CAR has a positive influence. Keywords: Stock Return, Financial Performance, Risk, Bank